Lexical Ambiguity in Gen Z's Digital Dialogue - Isabel Selmiola Sabrina; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study investigates the manifestation and resolution of lexical ambiguity within the unique communicative landscape of Generation Z. As digital natives, Gen Z frequently engages in multimodal and context-dependent communication, often embedding double meanings in everyday discourse for humor, identity expression, and social cohesion. Utilizing qualitative content analysis, this research analyzed instances of ambiguous lexical usage gathered from Gen Z-dominant social media platforms such as TikTok, Instagram, and Twitter. A corpus of 150 samples was selected and analyzed through the lens of discourse analysis and pragmatics. The findings reveal that Gen Z commonly employs lexical ambiguity in the form of polysemy and homonymy, relying on contextual cues, shared cultural knowledge, and digital semiotics (e.g., emojis and memes) to disambiguate meaning. These results underscore the dynamic and strategic nature of language in digital spaces, offering insights into Gen Z's sophisticated use of ambiguity as both a communicative tool and a marker of group identity.